Techniques in molecular medicine - Hildebrandt, Friedhelm (Springer Berlin Heidelberg Imprint: Springer, 1999)
To date, molecular biology techniques have been introduced to all fields of modern biomedical research and are now finding their way into diagnosis and even therapy. This laboratory manual is designed for researchers who have started or are planning to use molecular biology techniques and need reliable protocols for their laboratory work. It is also an ideal tool for teaching basic courses in molecular medicine. The well-described theoretical background of molecular biology also allows the understanding of the principles underlying these techniques. A wide range of topics, including purification, isolation, labelling, hybridization, sequencing and enzymatic modification of DNA or RNA, polymerase chain reaction, cloning, libraries, and protein techniques, are described for the immediate application in the laboratory
Gesehen am 06.04.2021